Replacing Metaphor with the Literal: A Case Study on Metaphysical Harm in Boston’s Museum of Fine Arts - Naar, Indigo R. (Tufts Archival Research Center, 2021)
In this capstone thesis paper for Visual and Material Studies, I argue that the Museum of Fine Arts (MFA) in Boston causes metaphysical harm to art via implicit and explicit forms of interpretation. I provide an understanding of the MFA’s history and practices, which I claim have led to several practices interpretation via text and display. I explore this claim through a case study of the exhibition “Women Take the Floor” (9/13/2019–11/28/2021), in which I examine the show as a whole, as well as the metaphysical affect the show has upon the objects in the exhibition.To account for the metaphysical harm done to art, I draw upon a recently developed philosophical school of thought: Object-Oriented Ontology (OOO). A central figure in the movement, Graham Harman, defines art as a compound object, one that cannot exist outside the aesthetic experience. Art is composed of an object and a beholder who is engaged with the object through an aesthetic experience, which is founded in a metaphoric relationship rather than a literal one. Drawing upon Harman’s considerations of aesthetics and objects, I argue that metaphysical harm is done to art when the metaphor supporting the aesthetic experience is replaced by a literal interpretation of the art. My definition of interpretation is drawn from selected writings of philosopher Susan Sontag, which argue that interpretation operates as a translation of art, which ultimately sublimates the true aesthetic nature of the art. I claim that interpretation as described by Sontag causes metaphysical harm to the art itself through the framework I adapt from Harman, and can occur through explicit and implicit means within the context of a museum, such as Boston's Museum of Fine Arts.; Submitted to the School of the Museum of Fine Arts.; Advisor: Silvia Bottinelli.